Pre-service teachers' attitudes towards children with disabilities: An Irish perspective. (May 2015) - Tindall, Daniel; MacDonald, Whitney; Carroll, Edith; Moody, Brigitte
The purpose of this study was to examine the impact of a 10-week adapted physical activity programme on the attitudes and perceptions of 64 Irish pre-service teachers (aged 19–25) towards teaching children and young people with physical, intellectual, and learning disabilities. Data were collected through written pre-programme expectations, weekly reflective logs, and a final written reflection. Data were analysed qualitatively through reading and rereading the data sources, identifying similarities and differences, themes, and patterns. Results revealed a positive change in attitude and perception toward both the idea of inclusion and working with persons with disabilities. Specifically, pre-programme anxieties diminished, confidence increased, and the benefits of the programme design (combining theory and practice) were realised. The findings of this study support the continued implementation of this type of 'lived' learning experience as an integral part of physical education initial teacher education programming in Ireland.